In Mrs. Tully's room : a childcare portrait - Paley, Vivian Gussin, 1929-2019 (Harvard University Press, 2001)
Focusing on a single childcare centre, this book shows how the providers combine teaching ability and emotional responsiveness to help even the smallest children learn words, concepts, stories, and the management of their emotions.